Progestin therapy to prevent preterm birth: History and effectiveness of current strategies and development of novel approaches. (April 2019) - Mesiano, Sam A.; Peters, Gregory A.; Amini, Peyvand; Wilson, Rachel A.; Tochtrop, Gregory P.; van Den Akker, Focco
Abstract: In the 1930s the "progestin" hormone produced by the corpus luteum was isolated and found to be a Δ 4 -keto-steroid. It was aptly named progesterone (P4) and in the following 30 years the capacity of P4 and derivatives to prevent preterm birth (PTB) was examined. Outcomes of multiple small studies suggested that progestin prophylaxis beginning at mid-gestation decreases the risk for PTB. Subsequent larger trials found that prophylaxis with weekly intramuscular injections of 17α-hydroxyprogesterone caproate (17HPC) beginning at mid-gestation decreased PTB risk in women with a history of PTB. Other trials found that daily vaginal P4 prophylaxis, also beginning at mid-gestation decreased PTB risk in women with a short cervix. Currently, prophylaxis with 17HPC (in women with a history of PTB) or vaginal P4 (in women with a short cervix) are used to prevent PTB. Recent advances in understanding the molecular biology of P4 signaling in uterine cells is revealing novel progestin-based targets for PTB prevention. One possibility is to use selective P4 receptor (PR) modulators (SPRMs) to boost PR anti-inflammatory activity that blocks labor, while simultaneously preventing PR phosphorylation that causes loss of P4/PR anti-inflammatory activity. This may be achieved by SPRMs that induce a specific PR conformation that prevents site-specific serine phosphorylation that inhibits anti-inflammatory activity. Further advances in understanding how P4 promotes uterine quiescence and how its labor blocking actions are withdrawn to trigger parturition will reveal novel therapeutic targets to more effectively prevent PTB. Highlights: A strong rationale exists for progestin-based therapies to prevent preterm birth. Progestin prophylaxis for preterm birth prevention is ineffective in most women. Next generation therapies may involve selective P4 receptor modulators (SPRMs). SPRMs that boost progesterone anti-inflammatory activity my prevent preterm birth.